Feeding Ecology of Philemon buceroides to Support Its Conservation Strategy - M. Yamin; Khairuddin Khairuddin; I Wayan Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Understanding food ecology is essential for conserving wildlife because feeding resources directly influence species survival, habitat use, and ecosystem functioning. This information is particularly important for endemic and habitat-dependent birds in tropical dry forests, where environmental changes may threaten food availability. This study aimed to analyze the feeding habits of P. buceroides in Taman Buru Pulau Moyo and evaluate their implications for conservation management. Field observations were conducted at four habitat types: primary forest, forest edge, plantation area, and savanna. Vegetation sampling was performed using 50 m × 50 m quadrats to document plant species composition and potential food resources. Data collected included vegetation characteristics, food plant species, feeding frequency, and resource utilization by P. buceroides. Vegetation data were analyzed using the Important Value Index (IVI), while feeding behavior and dietary preferences were assessed descriptively and qualitatively. The results showed that P. buceroides primarily feeds on nectar and fruits, with insects serving as supplementary food sources. Several flowering and fruit-bearing plant species were identified as key food resources supporting the species within the tropical dry forest ecosystem of Pulau Moyo. Feeding activities varied temporally, reflecting fluctuations in resource availability across habitats and observation periods. These findings highlight the ecological dependence of P. buceroides on specific plant species and emphasize the importance of maintaining habitat heterogeneity and protecting critical food plants. The study provides baseline ecological information that can support habitat management and conservation strategies for sustaining P. buceroides populations in Pulau Moyo and similar tropical dry forest ecosystems.